Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/anie.201104604
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic X‐Ray Diffraction Computed Tomography Reveals Real‐Time Insight into Catalyst Active Phase Evolution

Abstract: Dedicated to the Fritz Haber Institute, Berlin, on the occasion of its 100th anniversary Metals and metal oxides anchored to porous support materials are widely used as heterogeneous catalysts in a number of important industrial chemical processes. These catalysts owe their activity to the formation of unique metal/metal oxide support interactions, typically resulting in highly dispersed actives stabilized in a particular electronic or coordination state. [1][2][3] They are employed in fixed-bed reactors as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…176 It has been applied recently with a reasonable speed (acquisition of a slice in 20 min) for the study of structural change during high temperature modification of catalysts. 177 Alvarez-Murga et al 178 reviewed some recent results on diffraction/scattering computed tomography. They showed that the method yields an enhancement in the detection of the weak signals coming from minor phases.…”
Section: Chemical Tomographymentioning
confidence: 99%
“…176 It has been applied recently with a reasonable speed (acquisition of a slice in 20 min) for the study of structural change during high temperature modification of catalysts. 177 Alvarez-Murga et al 178 reviewed some recent results on diffraction/scattering computed tomography. They showed that the method yields an enhancement in the detection of the weak signals coming from minor phases.…”
Section: Chemical Tomographymentioning
confidence: 99%
“…In the in operando study the DSCT has been combined with absorption μCT offering a strong way to distinguish voids from areas composed of weakly scattering materials and relating high resolution imaging with the diffraction signals, this way revealing inactive parts of the catalyst body. 5,49,60 …”
Section: Examplesmentioning
confidence: 99%
“…In addition, new approaches are needed that effectively bridge the so-called materials and pressure gaps in our understanding of how to extend studies and phenomena observed in wellcharacterized systems to real-world applications. Continued advances in scanning probe techniques, 56 electron microscopy, 57 scattering and diffraction methods, 58 and high-pressure electron spectroscopies 59,60 will be critical tools in further advancing our understanding of the chemistry and physics of organic molecules on surfaces.…”
mentioning
confidence: 99%